PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTORSEKRETARIAT DPRD PROVINSI SUMATERA UTARA: PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTORSEKRETARIAT DPRD PROVINSI SUMATERA UTARA - Simanjuntak, Amanda; Iskandar, Dani (Journal Business and Management, 2024)
The purpose of this study was to determine and analyze the influence of Leadership and Work Environment on Employee Job Satisfaction at the DPRD Secretariat Office of North Sumatra Province. This study uses a quantitative approach with multiple linear analysis techniques. The results of the study show that leadership has an effect on job satisfaction, the work environment has an effect on job satisfaction. There is a significant influence between Leadership and Work Environment, on Job Satisfaction in Employees of the DPRD Secretariat Office of North Sumatra Province. So that if the Leadership and Work Environment are good, then Job Satisfaction can increase. Conversely, if leadership and work environment are low or decreased, job satisfaction will decrease. It is known that the R Square value is 0.549 or 54.9% indicating that around 54.9% the variable Job Satisfaction (Y) is influenced by Leadership (X1) and Work Environment (X2). The remaining 45.1% is influenced by variables not examined in this study.